POLA SPASIAL PERTUMBUHAN KAWASAN PERMUKIMAN DI DESA DALUNG - I Wayan Candrapraleka Putra W; Ngakan Ketut Acwin Dwijendra; I Dewa Gede Agung Diasana Putra (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2022)
An increase in population can lead to an increase in the number of space requirements while an increase in the number of space requirements can trigger the growth and development of an area. The growth is also experienced by Dalung Village with the potential that characterizes the embryo of an urban area, one of which has very high accessibility. Thus, future developments in Dalung Village will experience settlement compaction which will trigger the growth of slum areas and traffic congestion in the future. For this reason, this study aims to analyze the growth pattern of residential areas in Dulung Village. The research method used is descriptive qualitative to describe the spatial pattern of the growth of residential areas in Dulung Village. The analysis used is morphological analysis, which is used to identify the physical space in Dalung Village. The types of data that will be used in this study are the types of primary data and secondary data. The results of the analysis of this study indicate that the growth pattern of residential areas in Dalung Village is seen from the spatial shape of the city's morphology which tends to be in the form of an octopus because it is influenced by the development of existing transportation routes, while the development of the morphology of the settlement area in Dalung Village tends to be more elongated / ribbon because the development of settlements in Dalung Village occurs because of the transportation route.